KESIAPAN DESA TANJUNG TERDANA KABUPATEN BENGKULU TENGAH DALAM PENGELOLAAN ALOKASI DANA DESA (ADD) - Nursanty -; Yorry Hardayani; Loesida Roeliana (UNIVED PRESS, Universitas Dehasen Bengkulu, 2016)
This study aimed to see the readiness of Tanjung Terdana village in funds management on the Village Fund Allocation. The readiness could be seen from four aspects, namely: 1) device regulations/guidelines for the implementation readiness, 2) Human Resources readiness, 3) governance readiness, 4) Participation of the community. The results showed that although at first Tanjung Terdana village did not understand about the concept of financial management in particular the Village Fund Allocation which nominal was much greater than before, but they had the commitment and progress to develop the village by utilizing the Village Fund Allocation. So even though the implementing regulations at the local level was slow set so that governance couldn’t be run in accordance with a predetermined schedule, but head of the village and village officials consulted to a number of parties. Their willingness to learn, correct errors, effort, and along with community participation then slowly increased their readiness on managed the Village Fund Allocation.